1999
DOI: 10.1007/s007870050093
|View full text |Cite
|
Sign up to set email alerts
|

Parent reported preschool attention deficit hyperactivity: measurement and validity

Abstract: This is a two stage community study of 320 preschool children aged between two and a half to five years. An Attention Deficit Hyperactivity Scale (ADH-P) was constructed. A first stage sample was screened by asking parents to fill in the ADH-P and the Behaviour Check List (BCL) for behaviour problems; 116 children were included in the second stage. Reliability of the ADH-P was tested and found to be satisfactory. Its validity was also supported by teacher's report and clinical observation. Based on the parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
(39 reference statements)
0
16
1
Order By: Relevance
“…[15][16][17][18][19][20][21] A review of the literature, including the multisite study of the efficacy of methylphenidate in preschool-aged children, revealed that the criteria could appropriately identify children with the condition. 11 However, there are added challenges in determining the presence of key symptoms.…”
Section: Special Circumstances: Preschoolaged Children (4 -5 Years Old)mentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21] A review of the literature, including the multisite study of the efficacy of methylphenidate in preschool-aged children, revealed that the criteria could appropriately identify children with the condition. 11 However, there are added challenges in determining the presence of key symptoms.…”
Section: Special Circumstances: Preschoolaged Children (4 -5 Years Old)mentioning
confidence: 99%
“…For adolescents (12)(13)(14)(15)(16)(17)(18) years of age), the primary care clinician should prescribe Food and Drug Administration-approved medications for ADHD with the assent of the adolescent (quality of evidence A/strong recommendation) and may prescribe behavior therapy as treatment for ADHD (quality of evidence C/recommendation), preferably both.…”
mentioning
confidence: 99%
“…For instance, Egger, Kondo, and Angold 12 found that many preschoolers met school-age cutoff criteria for the symptoms of "often loses temper" (30%), "often interrupts or intrudes" (47%), and "often actively defies" (57%), respectively. Moreover, Pavuluri and colleagues 51 found that parents rated 48% and 65% of preschoolers as "often easily distracted" and "often talking excessively," respectively. Although this is particularly true for ODD and ADHD, even some CD symptoms that are generally defined as more serious, low-incidence behaviors may be prevalent in young children.…”
Section: Dbds and Adhd: Applying A Developmental Analysismentioning
confidence: 99%
“…A smaller room such as a group room where group work could be organised was considered to be positive. But as the studies by Charlop et al (1983), Pavuluri et al (1999), Cuckle and Wilson (2002), and Singhania (2005) also show, group work was considered as time consuming and difficult to pursue. According to Doctoroff (2001), the materials and equipment necessary for a learning task need to be accessible, which in this case means they could support these children successfully through the whole of the basic emotional process (Laike 1997).…”
Section: General Influences At An Overall Levelmentioning
confidence: 99%